2018
DOI: 10.5535/arm.2018.42.5.773
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Accessory Nerve Injury Induced by Manipulation Therapy: A Case Report

Abstract: Spinal accessory nerve (SAN) injury mostly occurs during surgical procedures. SAN injury caused by manipulation therapy has been rarely reported. We present a rare case of SAN injury associated with manipulation therapy showing scapular winging and droopy shoulder. A 42-year-old woman visited our outpatient clinic complaining of pain and limited active range of motion (ROM) in right shoulder and scapular winging after manipulation therapy. Needle electromyography and nerve conduction study suggested SAN injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The patient was informed that spontaneous recovery is uncommon according to the current literature; however, the pathology tends to present following invasive trauma unlike in his presentation. In the available literature discussing similar cases in terms of the nature of the causative pathology being high compressive pressure leading to nerve palsy, we found that they were all managed nonsurgically and showed some improvement; however, in the majority, residual weakness or functional limitation was evident on last follow-up ( Table 1 ) [ 4 , 5 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The patient was informed that spontaneous recovery is uncommon according to the current literature; however, the pathology tends to present following invasive trauma unlike in his presentation. In the available literature discussing similar cases in terms of the nature of the causative pathology being high compressive pressure leading to nerve palsy, we found that they were all managed nonsurgically and showed some improvement; however, in the majority, residual weakness or functional limitation was evident on last follow-up ( Table 1 ) [ 4 , 5 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 97%
“…A clear relationship between SANP and a history of neck dissection or lymph node excision was reported in the literature; in addition, other causes have been reported due to blunt trauma, such as deep tissue massage, lifting heavy objects, motor vehicle accidents, falls, and, more rarely, spontaneous onset [ 3 10 ]. In our case, the patient underwent spinal adjustment by a self-claimed experienced chiropractic specialist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying structures such as internal jugular vein, spinal accessory nerve, or thoracic duct are highly susceptible to injury, especially in early and very fibro-contracted SCM. 12 13 Though, it is also difficult to wait until patients are older because secondary disability due to CMT can be exacerbated. Facial asymmetry, one of the most well-known secondary disorders of CMT, occurs due to prolonged unilateral contracture of the SCM muscle and several reports have revealed that early release of SCM (before the age of 5 years) can facilitate better correction of craniofacial asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical environment of the infant head and neck is very narrow and small. The underlying structures such as internal jugular vein, spinal accessory nerve or thoracic duct are highly susceptible to injury, especially in early and very fibro-contracted SCM [12,13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%